(untitled) (American Journal of Technology and Applied Sciences, 2025)
The employee shall not be transferred to another job if there are contraindications for the employee based on his/her health status, confirmed by a medical report.When transferring an employee to another job, the date by which he/she must begin the work he/she is transferred to must be determined.